The Giants Awake: The Present and Future of Higher Education Systems in China and India - Philip Altbach (Arizona State University, 2014)
China and India are now the largest and third largest academic systems in the world-the United States is second. They are growing rapidly-much of the global enrolment expansion between now and 2050 will be in just these two countries.  China enrolls around 22 percent of the age cohort and India only 10 percent-thus there is much room for growth. Both India and China continue to the largest "exporters" of students-mainly to the large English-speaking academic systems. Each country has had a different approach to higher education development. India has failed to build top quality universities-only the Indian Institutes of Technology are recognized as "world class" institutions-and these are small and specialized. Most of India's energy has gone into provide access to students. China, on the other hand, has in the past two decades devoted much effort and funding to building a top tier of research universities and now has a dozen or more successful institutions that are beginning to compete successfully globally. Both countries have growing private higher education sectors, and both face considerable challenges as they try to serve a growing demand for access.